2001
DOI: 10.1007/s11663-001-0100-0
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of ceria as an actinide surrogate in electroslag remelting and refining slags

Abstract: Downsizing and decommissioning of nuclear facility operations is increasing the stockpile of various different grades of radioactive scrap iron (RSI). Disposal of this material not only represents significant resource and value lost but also necessitates long term monitoring for environmental compliance. The latter results in additional recurring expense. It is desirable to be able to decontaminate the RSI to a very low level that can be recycled or used for fabrication of containers for RSI disposal instead o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…Also, the high affinity of Ti and V for N lead to the formation of (TiV)N inclusions. The presence of TiO 2 at the high temperatures in the slag (1700-2000 o C) [33] and the addition of Al metal allow the reduction of TiO 2 through an exothermic aluminothermic reduction reaction [34,35] as in equation (4). Subsequently, once the Ti reaches the molten metal pool, TiN, (TiV)N, and TiO 2 are formed thereby explaining the presence of these types of inclusions in the ESR material while they are absent from the IF material.…”
Section: Chemical Composition Of Nmismentioning
confidence: 99%
“…Also, the high affinity of Ti and V for N lead to the formation of (TiV)N inclusions. The presence of TiO 2 at the high temperatures in the slag (1700-2000 o C) [33] and the addition of Al metal allow the reduction of TiO 2 through an exothermic aluminothermic reduction reaction [34,35] as in equation (4). Subsequently, once the Ti reaches the molten metal pool, TiN, (TiV)N, and TiO 2 are formed thereby explaining the presence of these types of inclusions in the ESR material while they are absent from the IF material.…”
Section: Chemical Composition Of Nmismentioning
confidence: 99%
“…Based on the results of the non-metallic inclusion analysis, the non-metallic inclusions were divided into five size categories and seven chemical composition categories: Chang et al [19] reported that there can be an oxygen increase in the ESR ingot due to the decomposition of oxides in the slag. The high temperatures that occur during the ESR process are up to 2000 °C [23] and are therefore thermodynamically suitable for oxide decomposition. Further analysis of the inclusions confirmed that there is a decrease in the number of inclusions after the ESR process.…”
Section: Resultsmentioning
confidence: 99%
“…The resistivity of the slag causes joule heating and is the main driving force behind the process. Joule heating through a molten slag layer maintains the slag temperature between 1700 °C and 2000 °C and melts one end of the electrode [23].…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis was verified by experimental results that higher vacuum (3400 Pa) applied on ceria pellets resulted in complete weight recovery of ceria pellets. Due to plutonium oxide's similar chemical properties to ceria [5][6][7], it is expected that bulk plutonium oxide will not dissolve in this molten salt process. This result indicates the feasibility of the molten salt corrosion method in which SiC is corroded in K 2 CO 3 molten salt to form the water soluble silicates but ceria is unchanged at 1050°C.…”
Section: Corrosion Of Ceria In the Molten Carbonatesmentioning
confidence: 99%
“…Ceria, a widely used surrogate of plutonium oxide (PuO 2 ) [5][6][7], can be filtered from a solution of water-soluble SiC corrosion products (e.g., potassium silicate) formed by SiC corrosion in the molten carbonates. Several parameters which may affect the SiC corrosion rate are also reported in this paper.…”
Section: Introductionmentioning
confidence: 99%